Fermentación de cacao y su efecto en la concentración de metales pesados - Ruiz Soliz, Luis Eduardo (2024)
This document details cocoa fermentation and its effect on the concentration of heavy metals, where the general objective was to establish the importance of cocoa fermentation and its effect on the concentration of heavy metals. The writing of the document was carried out with a compilation of updated information, including scientific articles, websites and virtual libraries, which provide perspectives and concepts from various authors, which facilitated the analysis of the current research process considered as a non-experimental research of bibliographic nature, using techniques of synthesis, analysis and summary of the information collected. The conclusions determined that heavy metals disturb physiological processes, resulting in decreased plant growth and a reduction in productivity, which negatively affects seed fermentation; Furthermore, during the post-harvest process it can present significant concentrations of cadmium, lead, nickel and arsenic, which affects the organoleptic quality and can induce deterioration in the cocoa kernel. Fermentation favors the enzymatic decomposition of proteins and carbohydrates present in the bean, which in turn promotes the development of the characteristic flavors and aromas of cocoa. There are various options for cocoa fermentation, the most significant being heap fermentation, which involves placing fresh almonds on perforated musaceae leaves or another type of material that acts as a separator between the almonds and the soil, facilitating the process. of deburring. This method is used by small producers due to its simplicity of execution and low cost.